Improved outcomes in paediatric laparoscopic anorectoplasty for ano-rectal malformations using enhanced recovery after surgery protocols: A study from Central India - Roshni Rai; Himanshu Acharya; Bharath Shiva; Abhishek Tiwari; Rajpal Singh Sisodiya; Vikesh Agrawal; Dhananjaya Sharma; Jagmohan Singh Dhakad (Journal of Pediatric Surgery Open, 2023)
Background: The revolutionary concept of using the body's innate stress response to surgery to access the advantage of early recovery in the postoperative period has changed the overall outcome of health systems of LMICs in terms of cost-effectiveness and increased patient turnover. Hence, is now the standard of care in many adult surgical specialities, but with very little evidence in paediatric surgical fields. This lacuna in the knowledge was identified and addressed which yielded positively comparable results. Methods: This is a retrospective and prospective validation study conducted in the Department of General Surgery, Netaji Subhash Chandra Bose Medical College and Hospital, Jabalpur, Madhya Pradesh, India between 1st March 2020 - 30th May 2022. The peri‑operative parameters affecting convalescence after surgery were reviewed and the results of the conventional peri‑operative protocols were compared with the ERAS group. Results: 50 patients with Ano-rectal malformations underwent laparoscopic anorectoplasty, of which 25 patients were treated with conventional peri‑operative protocol and 25 were treated with ERAS protocol. The results obtained were comparable and effective with the existing results in adult surgical specialities and also were statistically significant in most of the parameters. Conclusion: Shorter hospital stay reduces the financial burden alleviating both the physical and psychological stress of the patients and their parents. Also, judicious use of the available resources can increase the patient turnover of the existing health systems with the same financial assistance.